FAKTOR-FAKTOR PENTING DALAM STRATEGI PEMASARAN BATIK DI LESOENG BUTIK & BATIK PONOROGO - Diponegoro Al Fatih; Siti Chamidah; Wahna Widhianingrum (LPPM Universitas Bina Bangsa, 2022)
The aims of the study were to determine the marketing strategy used in selling batik at Lesoeng Butik & Batik Ponorogo and to determine the important factors in the marketing strategy of batik at Lesoeng Butik & Batik Ponorogo. The research used descriptive-analytic research, specifically with qualitative analysis. The data analysis technique used in this qualitative analysis has four stages, namely data collection, data reduction, data presentation and the last step is making conclusions. The results showed that the marketing strategy used by Batik Lesoeng was in addition to maximizing product quality, it also continues to find the tastes of OIM buyers (observe, imitate and modify), and use influencer services, especially exhibitions on the national and international scene. Among the five marketing strategy factors (Product, Price, Promotion, Place, and People) the most significant was the product factor. Second factor was the promotion factor or marketing communication, especially taking advantage of both national and international exhibition arenas. The third factor was the place factor that not only involving local markets, but big cities in Indonesia